Indonesia & Thailand: “Maltreatment”/ “Forced Labor”/ “TIP” in fisheries in Indonesia/Thailand - Sukonthapan, Pisawat (Indonesia Law Review, 2016)
This article focuses on “trafficking in persons” (TIP) in fisheries in Indonesia and Thailand. This The article refers to key international instruments on TIP and continues by discussing recent cases of TIP in fisheries in Indonesia that were reported in the first half of year 2015. It also explores national domestic legislation of Indonesia and Thailand in relation of measures to combat trafficking in the region. Bilateral and multilateral treaties such as the Treaty between the Government of the Kingdom of Thailand and the Government of the Republic of Indonesia Relating to Extradition and the ASEAN Treaty on Mutual Legal Assistance in Criminal Matters are also addressed as cooperation tools which should be used by Indonesia and Thailand in prosecuting traffickers. To attain success in prosecuting law breakers and to be fair to all concerned, the author discourages those who are preoccupied with TIP from prejudging all unlawful acts as incidents of TIP since many of them might not fall under the criteria of TIP. Additionally, the article addresses the U.S. Victims of Trafficking and Violence Protection Act of 2000, which classifies countries under one of the tiers stipulated therein. The author indirectly suggests that, via the Act, the U.S. puts pressure upon other countries to intensively suppress TIP and properly protect victims of TIP. Therefore, the author urges Indonesia and Thailand to take special care in handling incidents of TIP in fisheries.